2017
DOI: 10.1094/cchem-07-16-0189-r
|View full text |Cite|
|
Sign up to set email alerts
|

Variation and Correlation of Protein Molecular Weight Distribution and Semolina Quality Parameters for Durum Genotypes Grown in North Dakota

Abstract: Cereal Chem. 94(4):780-788This research assessed variation of protein molecular weight distribution (MWD) parameters and their correlations with quality characteristics of semolina samples that were obtained from durum genotypes grown in North Dakota. Sodium dodecyl sulfate buffer extractable and unextractable proteins in semolina were analyzed for MWD by size-exclusion HPLC with a microbore column. ANOVA indicated that quantitative variations of all the HPLC protein fractions were significantly (P < 0.001) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
17
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 25 publications
(89 reference statements)
10
17
3
Order By: Relevance
“…Pasta firmness both at 12 min and after cooking also showed similar trend of correlations that EF3 and EF4 had negative correlations whereas UF1‐UF3 showed significant positive correlations. Similar genotypic correlations were also reported for durum genotypes by Ohm et al (). Thus, the decrease of specific extractable proteins and the increase of specific extractable protein fractions over the years may have contributed toward improved dough quality that is observed in durum wheat cultivars released in later years.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Pasta firmness both at 12 min and after cooking also showed similar trend of correlations that EF3 and EF4 had negative correlations whereas UF1‐UF3 showed significant positive correlations. Similar genotypic correlations were also reported for durum genotypes by Ohm et al (). Thus, the decrease of specific extractable proteins and the increase of specific extractable protein fractions over the years may have contributed toward improved dough quality that is observed in durum wheat cultivars released in later years.…”
Section: Resultssupporting
confidence: 89%
“…Consequently, the shift of protein composition could be associated with improvements in protein quality, which has resulted in improved dough mixing properties and pasta cooking quality in durum wheat cultivars released in recent years. These results further support the findings of Edwards et al (2007), Edwards, Mulvaney, Scanlon, and Dexter (2003), Sissons, Ames, Hare, and Clarke (2005); Sissons, Egan, et al (2005) and Ohm et al (2017) who reported similar observations for durum wheat protein composition and quality. Although in general breeding efforts are not primarily focused on improving end-use quality traits, selection that occurred during the wheat breeding process may have contributed toward the observations made in this study.…”
Section: Se-hplc Analysis Of Gluten Proteins and Associations Of Prsupporting
confidence: 92%
See 1 more Smart Citation
“…The main gliadin fractions showed a negative partial correlation with loaf volume and positive correlations with water absorption parameters. Ohm, Manthey, and Elias () investigated the association between protein molecular weight distribution and quality traits in durum wheat and found that SDS‐unextractable glutenin polymeric proteins show positive correlations with mixograph characteristics and cooking characteristics, whereas SDS‐extractable gliadins show negative correlations with the same parameters. Chaudhary, Dangi, and Khatkar () also performed similar studies regarding molecular weight distribution and quality using bread wheat and found that glutenin fractions show positive correlations with dough development time, dough stability, and loaf volume.…”
Section: Resultsmentioning
confidence: 99%
“…Accession with higher G 0 and G 00 may result into higher cooked spaghetti firmness. A positive correlation of cooked spaghetti firmness with unextractable polymeric protein by Ohm et al (2017) and of unextractable polymeric proteins with G 0 and G 00 by Singh et al (2016) was observed. The storage of 107 kDa PP in EC577687 and lack of 40 and 38 kDa PPs in EC577687 and IC75208 may be responsible for lower G 0 and G 00 ( Fig.…”
Section: Mixographic Propertiesmentioning
confidence: 79%